A Reactivity Study of 4-Hydroxy-2H-chromene-2-thione and 4-Hydroxy-2H-thiochromene-2-thione with tert-Butyl Nitrite and Aromatic Amines: An Environmentally Benign Synthesis of New Hydrazone Derivatives - Xalxo, Anjela; Goswami, Ujjwal Jyoti; Das, Chiranjit; Mehta, Kriti; Bharatam, Prasad V.; Khan, Abu T. (Synthesis, 2024)
The synthesis of biologically active coumarin-based hydrazone derivatives is achieved through a one-pot, three-component reaction of 4-hydroxy-2H-chromene-2-thiones with aniline derivatives and tert-butyl nitrite under solvent- and catalyst-free conditions in yields of 76–86%. Similarly, the reactions of 4-hydroxydithiocoumarins with aniline derivatives and tert-butyl nitrite under identical conditions provided the corresponding hydrazone products in 79–85% yield through a four-component reaction. It is observed in both cases that the C=S group at the C2 position is converted into a C=O moiety. However, the intermediate products derived from 4-hydroxydithiocoumarin react further with another aniline molecule leading to thioesters. 4-Hydroxy-2H-chromene-2-thione and 4-hydroxydithiocoumarin exhibit distinct reactivity pathways, resulting in the formation of two different types of product. In addition, quantum chemical analysis of the mechanistic steps show that this reaction is exergonic. This protocol offers broad substrate scope and tolerates various functional groups, leading to high product yields in short reaction times.
Keywords: 4-hydroxy-2H-chromene-2-thione; 4-hydroxydithiocoumarin; anilines; hydrazones; exergonic reaction